Sunburn - Lescroart, John T. (Signet, 2009)
As the country of Spain prepares for revolution, two couples--a husband and wife bored with the life they have drifted into, and a combative pair that relish every moment in life--find their lives forever changed by the arrival of a young American seeking his missing lover.